The Concept of Early Vascular Aging - N. V. Burko; I. V. Avdeeva; V. E. Oleynikov; S. A. Boytsov (Рациональная фармакотерапия в кардиологии, 2019)
The age is one of the main non-modified factors which reduces the elasticity of vessels and increases the appearance of atherosclerotic plaques. A number of studies have revealed that in some people, vascular changes occur at a younger age, while the presence of only classical risk factors does not explain the development of cardiovascular events in young people. This phenomenon is described as a syndrome of early, or accelerated, vascular aging (EVA). Aspects of this premature process include endothelial dysfunction, increased arterial stiffness, thickening of the intima-media complex and impaired dilatation of the central arteries, an increase of the reflected wave, hypertrophy of small vessels with a decrease in their lumen. Accelerated aging of the vascular wall increases the frequency of complications, therefore, recently "vascular age” is considered as an important predictor of individual risk of cardiovascular events. The review describes factors and mechanisms that trigger the process of EVA, genetic aspects of vascular damage and the biology of telomeres. Changes in hemodynamics and structural and functional properties of arteries during physiological and accelerated aging are presented. Currently, several indicators have been proposed that indicate arterial wall damaging and progression of vascular aging. The carotid-femoral pulse wave velocity is included in the list of indicators of subclinical target organs damage in ESH-ESC Guidelines for the management of arterial hypertension. The results of studies on the developing the new diagnostic markers for identifying individuals with "normal" or "early" ("accelerated") vascular aging are presented. Therapeutic strategies are aimed at decreasing the influence of factors that provoke EVA and include a non-pharmacological approach and medical intervention. The paper describes methods of therapeutic correction of the EVA syndrome.